Using Multiangle Scanning to Determine the Transversal Profile of a Carbon Ion Beam; Physics of Particles and Nuclei Letters; Vol. 20, iss. 5 - Grigorieva (Grigorjeva) A. A. Anna Anatoljevna; Bulavskaya A. A. Angelina Aleksandrovna; Bushmina E. A. Elizaveta Alekseevna; Vorobjev A. P.; Vasiljeva A. G.; Miloichikova I. A. Irina Alekseevna; Stuchebrov S. G. Sergey Gennadevich (2023, 2023)
Title screen